Multimodal Intelligent Information Presentation - Stock, Oliviero; Zancanaro, Massimo; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Intelligent Multimodal Information Presentation relates to the ability of a computer system to automatically produce interactive information presentations, taking into account the specifics about the user, such as needs, interests and knowledge, and engaging in a collaborative interaction that helps the retrieval of relevant information and its understanding on the part of the user. The volume includes descriptions of some of the most representative recent works on Intelligent Information Presentation and a view of the challenges ahead.
Life Like Characters -- Greta. A Believable Embodied Conversational Agent -- Multimodal Communication in Virtual Environments -- Generating Embodied Information Presentations -- Mobile Presentations -- Resource-Adaptive Personal Navigation -- Intelligent Interactive Information Presentation for Cultural Tourism -- Supporting Mobile Users through Adaptive Information Presentation -- Natural Language Generation -- Autobriefer: A System for Authoring Narrated Briefings -- Generating Tailored Worked-Out Problem Solutions to Help Students Learn from Examples -- Multilingual Personalized Information Objects -- Generating Multimedia Presentations from Plain Text to Screen Play -- Intelligent Information Presentation for Tutoring Systems -- Virtual and Augmented Reality -- Maintaining Visibility Constraints for View Management in 3D User Interfaces -- Simulation Meets Hollywood -- Presentation Technologies for People with Disabilities -- Future Directions -- Fusion and Coordination for Multimodal Interactive Information Presentation.
Keywords: LINGUISTICS; MULTIMEDIA SYSTEMS; COMPUTER SCIENCE; ARTIFICIAL INTELLIGENCE; TRANSLATORS (COMPUTER PROGRAMS).; COMPUTATIONAL LINGUISTICS; LINGUISTICS; COMPUTATIONAL LINGUISTICS; MULTIMEDIA INFORMATION SYSTEMS; USER INTERFACES AND HUMAN COMPUTER INTERACTION; ARTIFICIAL INTELLIGENCE (INCL. ROBOTICS).; LANGUAGE TRANSLATION AND LINGUISTICS